RETRACTED: PENGEMBANGAN SOAL UNTUK MENGUKUR KEMAMPUAN BERPIKIR TINGKAT TINGGI POKOK BAHASAN BARISAN DAN DERET BILANGAN DI KELAS IX AKSELERASI SMP XAVERIUS MARIA PALEMBANG - Lewy Lewy (Jurnal Pendidikan Matematika, 2011)
Retracted: Following a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Matematika to article entitled “Pengembangan Soal untuk Mengukur Kemampuan Berpikir Tingkat Tinggi Pokok Bahasan Barisan dan Deret Bilangan di Kelas IX Akselerasi SMP Xaverius Maria Palembang” Vol 5, No 1, pp. 58-73, January 2011, DOI: http://dx.doi.org/10.22342/jpm.5.1.821. This paper has been found to be in violation of the Jurnal Pendidikan Matematika publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Jurnal Pendidikan Matematika, Vol. 3, No. 2, pp. 14-28, July 2009, DOI: https://doi.org/10.22342/jpm.3.2.326., entitled "Pengembangan Soal untuk Mengukur Kemampuan Berpikir Tingkat Tinggi Pokok Bahasan Barisan dan Deret Bilangan di Kelas IX Akselerasi SMP Xaverius Maria Palembang". The document and its content had been removed from Jurnal Pendidikan Matematika, and reasonable effort should be made to remove all references to this article